The effect of darkness on vitamin D in adults. Issue 642 (April 1979) - Fairney, A.; Fry, J.; Lipscomb, A.
Abstract : Circulating 25-hydroxy vitamin D measurements were made on Caucasians in the Antarctic. Following a period of 3 months' complete darkness there was a significant fall in 25-hydroxy vitamin D values. These results emphasize the importance of u.v. light on skin synthesis of cholecalciferol and support the view that the geriatric and immigrant population should be adequately exposed to sunlight to prevent vitamin D deficiency.